Feminism Depiction in “The Story of An Hour” By Kate Chopin’s Short Story - Sinthya Dewi, Ida Ayu Made; Seri Malini, Ni Luh Nyoman; Krisnawati, Ni Luh Putu (Loquēla (Journal of Linguistics, Literature, and Education), 2023)
Women's voices in a struggle against oppression are still very minimal to be heard. The purpose of this research is to find out the representation of liberal feminism that is used in the utterances in the short story “The Story of an Hour” by Kate Chopin. This data was collected by qualitative method with documentation technique. The result of this study is the story contains about discrimination of women in marital status through the dialogue of the characters, paying attention to the behavior and actions of the characters in the story. The researcher found seven pieces of data that included the types of liberal feminism, such as equal liberty, equal right, and equal freedom. The conclusion of this study explains that the main character reflects liberal feminism. Mrs. Mallard as the main character implicitly feels unlucky in her marriage as a wife. In the end, she got her freedom back after her husband died.